Implementation of Psychodrama-Based Group Counseling to Overcome Communication Anxiety in High School Students - Sasono, Satria Ananta; Khan, Rosa Imani; Milasanty, Devi Asmindra (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This action research evaluates the effectiveness of psychodrama-based group counseling in reducing interpersonal communication anxiety among seven 11th-grade students at SMAN 3 Kediri, identified with high anxiety levels (PRCA-24 scores >70). Conducted over two cycles of Guidance and Counseling Action Research (PTBK), each 45-minute session incorporated warm-up, enactment, and sharing phases. Data were collected using a 24-item anxiety scale (Cronbach’s α = 0.87), observations, student reflections, and counselor evaluations, analyzed via descriptive statistics, N-Gain, Wilcoxon signed-rank tests, and thematic coding. Pre-intervention, the average anxiety score was 72.14. Post-Cycle I, it decreased to 55.57 (N-Gain = 0.22), with 43% of students reaching moderate levels. Cycle II refinements, including relatable scenarios and assertiveness training, reduced the average to 39.50 (N-Gain = 0.45, p = 0.018), with all students achieving moderate anxiety. Psychodrama’s experiential, group-based approach, aligned with Indonesia’s collectivist culture, fostered peer support and emotional resilience. This cost-effective, culturally sensitive intervention offers a replicable model for school counselors to enhance students’ communication skills and well-being, with implications for broader educational applications.